Cochrane Database of Systematic Reviews 2014
DOI: 10.1002/14651858.cd011197
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-based cardiac rehabilitation for adults with atrial fibrillation

Abstract: Exercise-based cardiac rehabilitation for adults with atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…The eight selected SRs were conducted by the Cochrane heart group 1217 or the Cochrane vascular group 18,19 between 2014 and 2018, and included 155 RCTs enrolling a total of 23,779 persons with CVD. Overall, the SRs were focused on heart failure, 12 coronary heart disease, 13 heart valve surgery, 14 non-ulcerative chronic venous insufficiency, 18 atrial fibrillation, 15 heart transplant, 16 intermittent claudication 19 and stable angina. 17 All studies analysed the effects of exercise-based interventions (supervised or unsupervised inpatient, outpatient and community or home-based programmes) performed alone or in combination with psychosocial or educational interventions, or both (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The eight selected SRs were conducted by the Cochrane heart group 1217 or the Cochrane vascular group 18,19 between 2014 and 2018, and included 155 RCTs enrolling a total of 23,779 persons with CVD. Overall, the SRs were focused on heart failure, 12 coronary heart disease, 13 heart valve surgery, 14 non-ulcerative chronic venous insufficiency, 18 atrial fibrillation, 15 heart transplant, 16 intermittent claudication 19 and stable angina. 17 All studies analysed the effects of exercise-based interventions (supervised or unsupervised inpatient, outpatient and community or home-based programmes) performed alone or in combination with psychosocial or educational interventions, or both (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The patients' mean age ranged from 45 to 81 years; however, in four reviews, the participants' mean age was not clearly stated. 14,15,18,19 Finally, a subgroup analysis according to gender was planned for four of the eight Cochrane SRs analysed, although the specific forest plots for those outcomes to be re-evaluated by the subgroup analysis were not reported. 12,14,15,17 The main characteristics of the included Cochrane SRs are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the arrhythmia itself is associated with lower exercise capacity and physical fitness . While multiple studies showed benefit in increasing cardiovascular fitness in this patient population with subsequent decrease in incidence or recurrences of AF episodes, only few have examined the impact of the arrhythmia on cardiac rehabilitation and fitness training without being able to evaluate the real impact of exercise based cardiac rehabilitation on mortality or cardiovascular adverse events …”
Section: Introductionmentioning
confidence: 99%
“…10 While multiple studies showed benefit in increasing cardiovascular fitness in this patient population with subsequent decrease in incidence or recurrences of AF episodes, 11,12 only few have examined the impact of the arrhythmia on cardiac rehabilitation and fitness training without being able to evaluate the real impact of exercise based cardiac rehabilitation on mortality or cardiovascular adverse events. 13 Accordingly, the aim of this study was to examine effects of AF on cardiac rehabilitation and associated outcomes. Specifically, we sought to evaluate the role of the fitness level at baseline as well as the degree of improvement among AF patients undergoing CR, and its effect on cardiac related morbidity and total mortality.…”
Section: Introductionmentioning
confidence: 99%